Development of Teaching Materials in the Form of E-Books Assisted by Professional Flip Pdf Applications with the Theme of Environmental Conservation to Empower Environmental Care Attitudes - Siti Elfrida Silviana; Lukman Nulhakim; Vica Dian Aprelia Resti (CV. Rayyan Dwi Bharata, 2023)
The development of an e-book with the help of a professional flip pdf application with the theme of environmental preservation is motivated by the learning objectives of Natural Sciences (IPA), including to foster a positive attitude and students' awareness of the importance of protecting the environment. Achievement of research objectives in e-book development to empower students' environmental care attitudes through a series of activities contained in e-book systematics. This research was conducted in December 2022. The research method used was Research and Development RD, the research design used Borg and Gall and used 7 of 10 simplified research stages, adjusted based on research and development needs, namely up to the product revision stage. The instrument used was a validation sheet for the validity test which was carried out by 3 validators namely teaching material experts, material experts and science subject teachers. The development of the e-book is carried out using indicators of environmental care, namely Basic Competency (KD) which is used according to the theme of environmental preservation, presentation of pictures and videos about the dangers of environmental pollution around students' residences, about orders to implement greenery and dispose of waste in its place, as well as case studies on environmental pollution. The results of the development of the e-book were then validated by 3 validators with an average percentage of 92.9% with the criteria of